Canadian Water Resources Journal / Revue canadienne des ressources hydriques - Canadian Water Resources Journal / Revue canadienne des ressources hydriques (Taylor & Francis, 2026)
The Canadian Water Resources Journal accepts manuscripts in English or French and publishes abstracts in both official languages. Preference is given to manuscripts focusing on science and policy aspects of Canadian water management. Specifically, manuscripts should stimulate public awareness and understanding of Canada's water resources, encourage recognition of the high priority of water as a resource, and provide new or increased knowledge on some aspect of Canada's water.
FI 0.32
Q3
Keywords: Medicine; Medicina; Ecología; Agua; Acuerdos transformativos; Transformative agreements; Gestión del agua en Canadá; Recursos hídricos; Conciencia pública